Policing and Prosecuting Sexual Assault Against Women of Color: Applying Critical Race Theory and Intersectionality Frameworks to Examine Arrest and Charging Decisions in Cases Involving Black and Latina Victims - Acquaviva, Brittany L. (Crime & delinquency, 2024)
Using Critical Race Theory and an intersectional framework, the present study focuses on the case processing of sexual assault (SA) incidents involving Black and Latina victims. Importantly, much of the prior literature assessing arrest and charging decisions have been whitewashed by failing to consider that the factors influencing the case progression of white victims’ SA experiences may not appropriately apply to women of Color. Oftentimes, this scholarship merely controls for victim and suspect race without considering how legal and extralegal incident and case factors may operate differently for victims of Color. The present study addresses this oversight.